Comorbid Patients with Abdominal Obesity and High Risk of Atrial Fibrillation: Correction of Modifiable Risk Factors as a Strategy of Primary Prevention (Prospective Study) - A. I. Olesin; I. V. Konstantinova; N. N. Tyuteleva; V. S. Ivanov (Фундаментальная и клиническая медицина, 2024)
Aim. To assess whether correction of modifiable risk factors is efficient to prevent atrial fibrillation (AF) in comorbid patients with abdominal obesity and premature atrial contractions.Materials and Methods. We enrolled 889 comorbid patients with abdominal obesity and premature atrial contractions, aged from 58 to 72 years (average age 66.4 ± 0.7 years). The duration of follow-up was 3 years. All patients underwent correction of potentially modifiable risk factors of AF (normalisation of body weight, blood pressure, blood glucose and lipid levels, cessation of smoking, elimination of physical inactivity) until their target values were achieved. Endpoints included maintenance of sinus rhythm or registration of AF. After the follow-up, all patients could be divided into two groups: 578 (65.02%) patients with incomplete correction of risk factors, 95 (10.69%) patients who achieved target values, and 216 (24.29%) without risk factor correction.Results. Within the first two years of follow-up, the frequency of AF did not differ significantly and was 85.29%, 94.32%, and 93.47% respectively. In patients who achieved target values of potentially modifiable risk factors for > 1 year, the ratio of actual to predicted development of AF during the 2nd and 3rd year of follow-up was 57.58% and 14.29%, respectively.Conclusion. In comorbid patients with abdominal obesity and premature atrial contractions, reduction of AF was observed exclusively in patients with successful correction of all potentially modifiable risk factors for ≥ 2 years.